Perfectionism: A Double-Edged Sword (Journal of Namibian Studies : History Politics Culture, 2023)
Perfectionism is a personality trait in which a person holds a belief that one can achieve perfection and should aim for it. Perfectionist is described as “Tyranny of Should” by Karen Horney in 1950 in which we bounce between what we are and what we should be. Perfectionism has both positive and negative effects. It has psychological, genetic, and social causes. It was first introduced as a unidimensional trait, now it is accepted as a multidimensional trait. This trait is beneficial when positive and if it is negative, it should be reframed into a positive one which is a healthy, adaptive one. With all these factors in mind, researchers have conducted various studies to explore various factors related to perfectionism. In this paper, investigators have discussed dimensions, causes, impact, and various ways to combat perfectionism. This is a qualitative study. This study is purely based on qualitative data. The data for this paper is collected from various articles, journals, books, and websites.